Lattice-based verifiable timed signature and application - CHEN Huiyan; WANG Qingnan; WANG Ke; TAN Shuncong; XIN Hongcai (Tongxin xuebao)
Aiming at the problem that current verifiable timed signature (VTS) schemes cannot effectively resist the threat of quantum computing attacks, a lattice-based verifiable timed signature (LVTS) scheme was proposed, founded on challenging problems over lattices. This scheme not only fulfilled the fundamental criteria of unforgeability and privacy for verifiable timed signatures but also attained a heightened level of existential unforgeability in the random oracle model while ensuring the effective enforcement of privacy in hybrid argument. As a result, it exhibited exemplary security performance. Moreover, LVTS could be seamlessly integrated into electronic auction protocols (LVTS-EA) to enhance efficiency, security, and fairness in auction proceedings, offering an innovative and pragmatic solution for the electronic auction domain.